LEADERSHIP AS A MODERATOR: THE INFLUENCE OF SELF-EFFICACY AND BEHAVIORAL INTEGRITY ON INDIVIDUAL CREATIVITY - Juliasa, Made; Wardana, I Made Aditya; Adiandari, Ade Maharini; Aristana, I Nengah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This study aims to analyze the influence self-efficacy, behavioral integrity, and leadership towards individual creativity on Small and Medium Enterprises (SMEs) in Bali. A quantitative approach was used through a survey of 474 respondents consisting of managers and employees, with analysis using Partial Least Square – Structural Equation Modeling (PLS-SEM). The results of the study show that self-efficacy, behavioral integrity, and leadership have a positive and significant influence on individual creativity. These findings confirm that employee self-confidence, consistent behavioral integrity, and good leadership practices can encourage increased creativity. However, the analysis also indicates that leadership does not act as a moderating variable in the relationship between self-efficacy and behavioral integrity with individual creativity, but rather has a direct influence on creativity. Theoretically, this research strengthens the perspective socio cognitive theory which explains creativity as the result of the interaction between personal and environmental factors. Practically, the implications of this research encourage SME leaders to strengthen leadership capacity, foster employee self-confidence, and uphold behavioral integrity as strategies to increase competitiveness through individual creativity.